Pengelolaan Program Wirid Remaja dalam Pembentukan Karakter Islami Remaja di SMAN 1 Patamuan Padang Pariaman - Mawadah, Linta (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the management of wirid remaja programs as a method for developing Islamic character, despite their significant influence in character formation among students, particularly at SMAN 1 Patamuan, West Sumatra. The objective of this research is to analyze the management of the wirid remaja program in shaping students’ Islamic character. A descriptive qualitative method was employed, with purposive sampling involving the school principal, program coordinator, supervising teachers, and student participants. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The findings indicate that the program is managed effectively through systematic stages of planning, organizing, actuating, and controlling, which support the internalization of Islamic values such as honesty, discipline, responsibility, and mutual respect. Student participation was found to be high, though some challenges were addressed through innovative teaching methods and motivational strategies. These findings align with educational management theory and intrinsic motivation, emphasizing the importance of religious programs in character development. The study concludes that wirid remaja is an effective strategy for fostering Islamic character, with both theoretical and practical implications for the development of character education policy and opportunities for further research in broader contexts. Keywords: Internalization of Islamic Values; Wirid Remaja; Islamic Character; Adolescent Development; Educational Management